2005
DOI: 10.1021/pr050078k
|View full text |Cite
|
Sign up to set email alerts
|

Mass Tagging Approach for Mitochondrial Thiol Proteins

Abstract: A mass tagging approach is described for mitochondrial thiol proteins under nondenaturing conditions. This approach utilizes stable isotope-coded, thiol-reactive (4-iodobutyl)triphenylphosphonium (IBTP) reagents, i.e., the isotopomers IBTP-d(0) and IBTP-d(15). The mass spectrometric properties of IBTP-labeled peptides were evaluated using an ESI-q-TOF and a MALDI-TOF/TOF instrument. High energy collision induced dissociation (CID) in the TOF/TOF instrument caused side-chain fragmentation in the butyltriphenylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…A scenario is emerging in which the dielectric constant, surface accessibility and the modulation of the nucleophilicity and basicity of a certain residue by its microenvironment may govern the propensity of a distinct site to modifications by electrophiles (Roe et al, 2007; Sayre et al, 2006). In this context, various alkylating reagents have been employed to determine preferred target sites of modifications (Marley et al, 2005; Shin et al, 2007; Wong and Liebler, 2008). We explored the use of a sterically demanding butyltriphenylphosphonium group as a chemical tool for the identification of mitochondrial protein thiols that exhibit a large degree of surface accessibility (Marley et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A scenario is emerging in which the dielectric constant, surface accessibility and the modulation of the nucleophilicity and basicity of a certain residue by its microenvironment may govern the propensity of a distinct site to modifications by electrophiles (Roe et al, 2007; Sayre et al, 2006). In this context, various alkylating reagents have been employed to determine preferred target sites of modifications (Marley et al, 2005; Shin et al, 2007; Wong and Liebler, 2008). We explored the use of a sterically demanding butyltriphenylphosphonium group as a chemical tool for the identification of mitochondrial protein thiols that exhibit a large degree of surface accessibility (Marley et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, various alkylating reagents have been employed to determine preferred target sites of modifications (Marley et al, 2005; Shin et al, 2007; Wong and Liebler, 2008). We explored the use of a sterically demanding butyltriphenylphosphonium group as a chemical tool for the identification of mitochondrial protein thiols that exhibit a large degree of surface accessibility (Marley et al, 2005). In this study, Cys-385 of aconitase was readily alkylated by (4-iodo)butyltriphenylphosphonium iodide (IBTP).…”
Section: Resultsmentioning
confidence: 99%
“…The alkylation of mitochondrial proteins with IBTP was described previously [11]. Briefly, rat cardiac mitochondria were isolated according to Suh, et.…”
Section: Methodsmentioning
confidence: 99%
“…As a lipophilic and cationic reagent, IBTP is able to penetrate the lipid bilayers and accumulated inside the mitochondria due to the large membrane potential present across the inner mitochondrial membrane. Our group has explored the use of stable isotopically-coded IBTP probes in gel-free proteomics approaches to obtain site-specific information on reactive thiol groups in mitochondrial proteins [11]. During the course of these studies we observed that the introduction of the butyltriphenylphosphonium (BTP)-moiety affected the collision-induced dissociation (CID) behaviors of BTP-modified peptides which warranted further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…MALDI-MS/MS analysis was performed as described by Marley et al [18]. MALDI-MS/MS data were processed with GPS explorer 2.0 for creating MASCOT-searchable files as described [15].…”
Section: Msmentioning
confidence: 99%